A key management scheme with encoding and improved security for wireless sensor networks - Pathan, Al-Sakib Khan; Dai, Tran Thanh; Hong, Choong Seon (Springer-Verlag, Berlin, Germany, 2006)
Wireless sensor networks are emerging as a promising solution for various types of futuristic applications both for military and public. Security in wireless sensor networks is very crucial as these networks are expected mainly to operate in the hazardous and hostile environments. Efficient key management could guarantee authenticity and confidentiality of the data exchanged among the nodes in the network. In this paper, we propose an improved and efficient key pre-distribution scheme for wireless sensor networks. Our scheme significantly increases the storage efficiency and security than that of the previously proposed scheme based on LU decomposition. It also ensures node-to-node mutual authentication in a way that an eavesdropper cannot harm the network by monitoring the traffic flows in the network. We also present detailed performance analysis and compare our scheme with the existing schemes.